Motivations and Barriers for Veterinarians When Facilitating Fertility Management on UK Dairy Farms - Brocket, James John; Fishbourne, Emma; Smith, Robert Frank; Higgins, Helen Mary (Frontiers in Veterinary Science, 2021)
It is economically essential, but challenging, for dairy farmers to manage bovine fertility. Vets can help farmers to improve fertility, and this is cost-effective bringing benefits for production, animal health and welfare, and the environment. However, the extent to which vets are involved in fertility varies considerably between farms, for reasons that are unclear. This study investigated the motivators and barriers that vets perceive when trying to increase their involvement with fertility management on UK dairy farms. Interviews were conducted with 20 vets and four themes identified. The first, “clinical baggage,” highlighted vets' disillusionment due to past experiences of low uptake of their advice by farmers. Consequently, some vets made assumptions about farmer needs and behaviours, and exhibited ageist stereotyping. These issues, along with concerns and fatigue associated with repeatedly offering the same advice which was not acted upon, negatively influenced vets' engagement with farmers. The second theme “stuck in the comfort zone” revealed a loss of enthusiasm by some senior vets, whilst others lacked confidence to engage due to perceived gaps in their knowledge. Vets also reported farmers not perceiving their problems and lack of farm data or facilities, as barriers. The “vet-farmer relationship” theme highlighted building trust and developing strong relationships which were key drivers for vets to proactively engage and to “go the extra mile” for their clients. The final theme “money matters” explored vets' motivations to improve their clients' profitability and included the future sustainability of their own businesses. Our themes provide useful insight into the challenges vets face and provide key areas that can be targeted in future interventions to improve veterinary involvement in fertility management. For example, post-graduate training and support for vets needs to consider factors such as reflection, mentorship, stereotyping, relationships, communication, and leadership skills. This type of postgraduate support is currently limited for vets and requires investment from stakeholders if improvements in production, animal health and welfare, and the environment are to be achieved. Our findings are informative for facilitating veterinary involvement in any disease context, and are relevant for stakeholders including governments, educators, charities, farmer representatives, environmentalists, and veterinary leaders.